The Integration of ELSA Speak on English Pronunciation Skills in EFL University Students: A Systematic Literature Review - Winduastuti, Ni Komang; Utami, I G A Lokita Purnamika; Artini, Ni Nyoman (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This systematic review synthesizes and examines previous studies on the impact of ELSA Speak integration on the English language learning process towards the pronunciation skills of EFL students at the university level, by reviewing 11 relevant articles published between 2019 and 2025. This review adhered to the framework of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The findings of this study revealed that the integration of ELSA Speak significantly impacted the pronunciation skills of EFL students in higher education. In addition, ELSA Speak also contributes to increasing student motivation and supporting independent learning. Furthermore, features provided by ELSA Speak, such as real-time feedback and role-play speaking exercises, help students improve their speaking skills, especially their pronunciation skills.